Peranan penataan ruang untuk menanggulangi dampak transformasi struktur sosial-ekonomi dalam industrialisasi pada pembangunan jangka panjang Indonesia tahap II - Susilowati, Susilowati (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1994)
The Indonesia population lived in urban has in creased rapidly and the number will be 50% of the total Indonesia population in the second Phase Loug Term Development. Indutrialisation centered at town and the higher capacity of development at town become a power of attractionÂ for peopleÂ to move town. The diversity of culture, etnic, educationÂ and social level background make the manpowers with minimum capitals gathered in a slumÂ area and are not be able Â to be served by urban facilities, where as for the town it self, in this globalization era, towns which are served with International Communication facilities and the isolated areas. This situation and condition on makes the isolated areas willÂ be deeply isolated. It make possible an economic and social gap that is able to create an crime-infested. Prevention or at bast minindization of this can be strove by anÂ issue of an arrangement and goverment policy on the determination o f industrial-Â development Area thtought an arrangement of Area Lay â Outing, UURI No. 24, 1992 Concering âLay Outingâ.Â ABSTRAKÂ Proporsi penduduk IndonesiaÂ yang tinggal di daerah perkotaan terus meningkat dengan pesat, dan akan menjadi 50% dari total seluruh pendudukan Indonesia pada PJPT II. Industrialisasi yang terpusatÂ Â di kota dan hasil pembangunanÂ yang lebih tinggi di kota, merupakan daya tarik bagi penduduk untuk berurbanisasi ke kota. Dengan latar belakang perbedaanÂ budaya, etnis, pendidikan dan tingkat sosial yang beraneka ragam,Â makan tenaga kerja dengan modal minimÂ Â Â Â Â